Antimicrobial potential of Streptomyces isolates from Con Dao National Forest - Nguyet Thuong, Le Pham; Hoa Thien, Truong; Thi Hang, Tong (Vietnam Journal of Biotechnology, 2022)
Streptomyces are considered the most potential microbes with the ability to produce antimicrobial and anticancer agents. These bacteria are found mostly in soil across the globe and play a pivotal role in material recycling processes. Isolation of Streptomyces in Vietnam has been conducted for years. However, there are few investigations on protected regions which have very little exchanging activities. This project aims to explore the resource for antimicrobial activity of Streptomyces isolated from Con Son Island (Con Dao). Eighteen soil samples were collected in different surface lands in Con Dao and cleaned prior to culturing and isolation. Twenty-five isolates (named from C1 to C25) were obtained from ISP4 agar plates and stored in glycerol 30% at -80oC. Liquid cultures were established in 3 different media (ISP4, Gause I and TSB) for all isolates. Broth collected from cultures at stationary phase was extracted with ethyl acetate at the ratio 1:1 (v/v) followed with antimicrobial tests against three bacterial and two fungal microorganisms (S. aureus, B. subtilis, E. coli, C. albicans, A. parasiticus). Sixty percent of isolates show activity against at least one microbe. The isolates C13, C22 and C24 showed the ability to inhibit both bacteria and fungi tested. Results from C13 and C22 express remarkable activity to prevent the growth of B. subtilis and C. albicans, respectively. This study suggests the potential of Streptomyces from the investigated area and recommends more optimization of the culture condition as well as extractions with other solvents to get better antimicrobial activities.